THERAPEUTIC EFFECTS OF SALVADORA PERSICA EXTRACTS AGAINST SARCOPTES SCABIEI VAR. HOMINIS AND THEIR SECONDARY INFECTIONS - Abbas Shahid; Dr. Amina Arif; Ramisha Ali; Dr. Abdul Aziz; Mian Saeed Sarwar; Mehwish Naeem; Ayesha Nawaz; Syed Rizvan Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Salvadora persica, commonly recognized as the Miswak tree, happens in shrub savannah. From northwestern areas. The current evaluation gives a complete summary of the chemical materials and organic results (antibacterial and anti-parasitic specially scabies) of this species. To examine the qualitative and quantitative analyses of methanolic and ethanolic extracts to screen the phytochemical contents, sulfur containing compound present in Salvadora persica against scabies and secondary bacterial infection. Numerous compounds were identified using GCMS analysis, biological activities, Molecular docking and anti-bacterial activity of stem extracts. It contributes to widespread disease brought on by secondary bacterial infections and post-infectious conditions such acute post-streptococcal glomerulonephritis Sarcoptic scabies mites’ variant Hominis can be killed by sulfur-containing compounds. The extract of Salvadora persica have an effect against scabies and the subsequent bacterial infection inside the single dose. They can protect against secondary bacterial scabies infections. The potential interaction and binding affinity between ligands 2-(2 Methyl vinyl) thiophene, Benzene, (Isothiocyanatomethyl) and Benzyl Nitrile and protein (3h7t) were analyzed by Auto dockvina. The ligand tended to bind with the binding energy -4.3kcal/mol, -5.4kcal/mol and -5.7kcal/mol respectively.